Inhibition of myostatin improves muscle atrophy in oculopharyngeal muscular dystrophy (OPMD) - Pradeep Harish; Alberto Malerba; Ngoc Lu‐Nguyen; Leysa Forrest; Ornella Cappellari; Fanny Roth; Capucine Trollet; Linda Popplewell; George Dickson (Wiley, 2019)
Abstract Background Oculopharyngeal muscular dystrophy (OPMD) is a late‐onset muscle disease affecting one per 80 000 of the general population characterized by profound dysphagia and ptosis, and limb weakness at later stages. Affected muscles are characterized by increased fibrosis and atrophy. Myostatin is a negative regulator of muscle mass, and inhibition of myostatin has been demonstrated to ameliorate symptoms in dystrophic muscles. Methods In this study, we performed a systemic delivery of a monoclonal antibody to immunologically block myostatin in the A17 mouse model of OPMD. The mice were administered a weekly dose of 10 mg/kg RK35 intraperitonially for 10 weeks, following which histological analyses were performed on the samples. Results This treatment significantly (P < 0.01) improved body mass (11%) and muscle mass (for the tibialis anterior and extensor digitorum longus by 19% and 41%) in the A17 mice treated with RK35 when compared to saline controls. Similarly, a significantly (P < 0.01) increased muscle strength (18% increase in maximal tetanic force) and myofibre diameter (17% and 44% for the tibialis anterior and extensor digitorum longus), and reduced expression of markers of muscle fibrosis (40% reduction in area of expression), was also observed. No change in the density of intranuclear inclusions (a hallmark of disease progression of OPMD) was however observed. Conclusions Our study supports the clinical translation of such antibody‐mediated inhibition of myostatin as a treatment of OPMD. This strategy has implications to be used as adjuvant therapies with gene therapy based approaches, or to stabilize the muscle prior to myoblast transplantation.